2020
DOI: 10.1016/j.molmet.2020.101047
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic skin inflammation induces a pre-diabetic phenotype via the endocrine actions of skin secretome

Abstract: Objective Psoriasis is a chronic inflammatory skin disease that is thought to affect ∼2% of the global population. Psoriasis has been associated with ∼30% increased risk of developing type 2 diabetes (T2D), with numerous studies reporting that psoriasis is an independent risk-factor for T2D, separate from underlying obesity. Separately, studies of skin-specific transgenic mice have reported altered whole-body glucose homeostasis in these models. These studies imply a direct role for skin inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Several studies ( Gelfand et al, 2018 ; Tollefson et al, 2018 ; Evans et al, 2020 ) have shown that the pathogenesis of psoriasis is closely related to metabolic disorders that are frequently aggravated. The Gly-Ser-Thr axis is a major metabolic crossroad connecting several crucial biological pathways ( Aon et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies ( Gelfand et al, 2018 ; Tollefson et al, 2018 ; Evans et al, 2020 ) have shown that the pathogenesis of psoriasis is closely related to metabolic disorders that are frequently aggravated. The Gly-Ser-Thr axis is a major metabolic crossroad connecting several crucial biological pathways ( Aon et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Obesity is known to promote a proinflammatory state, which facilitates the manifestation of inflammatory skin diseases 70 . In contrast, inflammatory skin diseases, such as imiquimod‐induced psoriasis‐like lesions in mice, can induce reactions in pancreatic beta islet cells mimicking a prediabetic phenotype 71 . In this context, the first‐line antidiabetic biguanide metformin appears as a model‐drug in HS treatment 72,73 , affecting various indirect and direct pathways of inflammation or steroid receptor signalling, both in immune and epithelial cells 74 .…”
Section: Hormones and Metforminmentioning
confidence: 99%
“…Similar findings were reported by a study that used a mice model of psoriasis-like skin inflammation, which showed that a pre-diabetic phenotype displayed by compensating function of pancreas, and signs of metabolic dysfunction in subcutaneous and other multiple organs. 29 This preliminary study only reports the general distributions of glucose metabolic diversity between normal T2D patients and T2D with PsO in our hospital, therefore, there is need to explore the underlying molecular and genetic mechanism of PsO on the pathophysiology of T2D.…”
Section: Discussionmentioning
confidence: 95%